2002
DOI: 10.3354/cr021271
|View full text |Cite
|
Sign up to set email alerts
|

Climate variability and the vulnerability of ranching in southeastern Arizona: a pilot study

Abstract: For ranchers in the Southwest, unanticipated droughts pose serious management challenges. Social and economic factors combine with the physical impacts of drought to render ranchers more vulnerable to climate variability. Using agricultural census data and interviews with ranchers, we analyze ranchers' responses to drought events in 1996 and 1999. From this analysis we develop an initial assessment of the principal factors contributing to the vulnerability of ranching in southeastern Arizona to climatic variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 12 publications
5
26
0
Order By: Relevance
“…We were less certain, however, about what attributes of capacity (as defined in previous studies) would be present in this population. Other research in the state has shown, for example, that there is some disparity among farmers and ranchers in terms of access to resources and information, and participation in social networks that are instrumental in managing risk (Coles and Scott 2009;Eakin and Conley 2002;VasquezLeon et al 2003). And while irrigation buffers farmers from dealing with climatic and hydrological variability, its availability may also contribute to a sense of security that undermines the more cognitive dimensions of capacity, such as astute risk perception, self-efficacy, experimentation and learning (Brugger and Crimmins 2013).…”
Section: Discussionmentioning
confidence: 95%
“…We were less certain, however, about what attributes of capacity (as defined in previous studies) would be present in this population. Other research in the state has shown, for example, that there is some disparity among farmers and ranchers in terms of access to resources and information, and participation in social networks that are instrumental in managing risk (Coles and Scott 2009;Eakin and Conley 2002;VasquezLeon et al 2003). And while irrigation buffers farmers from dealing with climatic and hydrological variability, its availability may also contribute to a sense of security that undermines the more cognitive dimensions of capacity, such as astute risk perception, self-efficacy, experimentation and learning (Brugger and Crimmins 2013).…”
Section: Discussionmentioning
confidence: 95%
“…Wheat and sorghum on 42% of New Mexico's cropland are mainly dry land crops and are very seriously affected by droughts such as those of 1994-96 and 1998. The vulnerability of the ranching sector is discussed in detail by Eakin & Conley (2002) and is significant because of reliance on rain fed pasture, economic uncertainties and competition from Mexico. Concentrations of agricultural production within sectors or geographically also mean climatic variations can have more of an impact than if production were more dispersed over sectors or space.…”
Section: Implications For Land Management and Agricultural Vulnerabilitymentioning
confidence: 99%
“…Vulnerability assessment is now widely used as an effective way to facilitate the understanding of the interaction between hazards or disturbances and the exposed systems. Numerous studies have been done in many different scholarly fields including geography, agricultural science, water resource analysis, climate research and social sciences (Baethgen 1997;Eakin and Conley 2002;Descroix et al 2003).…”
Section: Introductionmentioning
confidence: 98%